CULTURAL HERITAGE PRESERVATION THROUGH COMMUNITY ENGAGEMENT A NEW PARADIGM FOR SOCIAL SUSTAINABILITY - Usmaedi; Lansiwi, Muhammad Amin; Studyanto, Anung B; Gymnastiar, Iman Ahmad; Amin, Fakhry (GoAcademica CRP, 2024)
Cultural heritage preservation is crucial for maintaining social sustainability, particularly through community engagement. This study examines the new paradigm of involving communities in the preservation of cultural heritage, exploring how their participation contributes to social sustainability. Utilizing a mixed-methods approach, this research includes qualitative interviews with community members and stakeholders, as well as quantitative analysis of preservation outcomes. Findings indicate that active community involvement enhances the effectiveness of preservation efforts, fosters a sense of ownership, and promotes cultural continuity. This paper aims to provide insights and practical recommendations for policymakers and heritage conservationists to strengthen community-based preservation initiatives.